Audiolingual Method in Arabic Learning - Ritonga, Mahyudin; Armini, Armini; Julhadi, Julhadi; Rambe, Muslim Hasonangan; Jaffar, Mohammad Najib (Universitas Islam Negeri Raden Intan Lampung, 2023)
Learning methods have an important position in achieving learning objectives. One of the reasons for the slow achievement of the goals that have been set is the inaccuracy in choosing the method. The Audiolingual method as applied by Arabic learning practitioners has been able to improve the quality of Arabic learning processes and outcomes. Therefore, this article explains, reveals, and analyzes in depth the Audiolingual method in theory and practice. The research was conducted with a qualitative approach. Research data were collected from library sources relevant to the research theme. The research data were analyzed in terms of content analysis by comparing various opinions of experts, the researcher concludes by determining the position among the existing opinions. The result of the research is the Audiolingual method, which is a language learning method that emphasizes understanding what is listened to. This method emerged based on the behaviorism approach. In practice, the Audiolingual method is equipped with exercises on sentence patterns that aim to improve student's communication skills. The findings can be further developed by further researchers by examining the use of the Audiolingual method in various educational institutions through action, development, or research in the form of evaluation.